Potential Flood Risk Scenario and Its Effects on Landscape Composition Using Hydraulic Modeling (HEC-RAS) in Boğaçay Sub-Basin/Türkiye - Serdar Selim; Emine Kahraman; Ceren Selim; Rifat Olgun; Nihat Karakuş; Erhan Önen; Mesut Çoşlu; Zeynep R. Ardahanlıoğlu; Mert Çakır; İsmail Çinar (Applied Sciences)
Flooding, one of the most destructive and recurrent natural catastrophes, causes severe loss of life and property. The destructive effect of floods has increased with climate change and unplanned urbanization. To prevent this devastation and find solutions to potential flooding, it is important to improve engineering, ecological, hydrological, and hydrogeological precautions, as well as potential flood simulations. Using hydraulic models to perform flood simulations is a common and successful approach globally. In this study, HEC-RAS (1D) was used to simulate three different flood scenarios on the Boğaçay sub-basin in Antalya, the most important tourism destination of Türkiye. Flood scenarios were developed based on the data of the floods that occurred in the region in 2003 and 2006, with measured flow rates of 1899.9 m3/s and 1450 m3/s, respectively, and with the maximum flow rate (2408 m3/s) determined by the relevant ministry. Then, the landscape composition of the region at the sub-basin scale was determined and the impacts of flood scenarios on the landscape composition around the riverbed were evaluated. The results of the analysis show that the water height will increase, ranging from 1.4 m to 3.6 m, and the landscape composition of the region will be significantly affected by this increase in water height in the three different flood scenarios. Especially in the part where the river meets the sea, 580.74 ha of urban settlement is estimated to be damaged by flooding, according to the worst-case scenario. Finally, the study will guide decision-makers to take the necessary measures under the relevant scenarios.